Piperacillin/tazobactam vs ceftazidime in the treatment of neutropenic fever in patients with acute leukemia or following autologous peripheral blood stem cell transplantation: a prospective randomized trial - Harter, Christoph; Schulze, Birte; Goldschmidt, Hartmut; Benner, Axel; Geiss, Heinrich K.; Hoppe-Tichy, Torsten; Ho, Anthony Dick; Egerer, Gerlinde (Bone marrow transplantation, 2006)
Piperacillin/tazobactam was compared with ceftazidime for the empirical treatment of febrile neutropenia in patients with acute leukemia or following autologous peripheral blood stem cell transplantation. Owing to inclusion criteria, it was possible for the same patient to be randomized several times. A total of 219 individual patients were admitted to a prospective randomized clinical study: 24 patients were included twice. Patients (23.5%) remained afebrile. Patients who developed febrile neutropenia were randomized to receive intravenous ceftazidime (n=74 patients, group I) or piperacillin/tazobactam (n=87 patients, group II). Response to first-line antibiotic treatment was seen in 55% (group I) and 53% (group II). After the addition of vancomycin, a further 19% (group I) and 24% (group II) of the patients became afebrile. Causes of fever were: microbiologically documented infection in 36 and 34 patients of group I and II; Clostridium difficile in eight and 12 patients of group I and II, and fever of unknown origin in 30 and 41 patients of group I and II. One patient died in each group. Single-agent therapy with piperacillin/tazobactam is as effective as ceftazidime in the treatment of neutropenic fever and is well tolerated. Direct and indirect costs of both treatment regimes are equivalent.
Gesehen am 05.11.2021